Efficacy of Glucomannan-Containing Yeast and Glucomannan Extracted from Amorphophallus oncophyllus Against Aflatoxins in Broiler Chicken - Susanto , Agus; Laconi, Erika B.; Astuti, Dewi Apri; Bahri, Syamsul (International Journal of Poultry Science, 2015)
The objective of the study was to evaluate and compare the efficiency of glucomannan extracted from Amorphophallus oncophyllus (GRE) with commercial aflatoxin binder glucomannan yeast product (GYP) in broiler chicken fed aflatoxin contaminated feed. A total of 63 one day old chicks were assigned to 9 equal groups according to dietary treatments: A (basal feed), B (basal feed+aflatoxin 50 μg/kg), C (basal feed+aflatoxin 2 mg/kg), D (basal feed+aflatoxin 50 μg/kg+GYP 1 g/kg), E (basal feed+aflatoxin 50 μg/kg+GRE 1 g/kg), F (basal feed+aflatoxin 50 μg/kg+GRE 2 g/kg), G (basal feed+aflatoxin 2 mg/kg+GYP 1 g/kg), H (basal feed+aflatoxin 2 mg/kg+GRE 1 g/kg) and I (basal feed+aflatoxin 2 mg/kg+GRE 2 g/kg). The body weight decreased significantly (p<0.05) with the inclusion of aflotoxins in the diet at 2 mg/kg diet. Both GYP and GRE were found almost equally effective in combating the negative impact by improving the body weights. Feed intake and FCR of birds fed basal diet with aflatoxin at 2 mg/kg decreased significantly (p<0.05) when compared to the control. Supplementation of both GYP and GRE improved the feed intake and FCR of broiler chicken. Aflatoxins at 2 mg/kg (group C) significantly (p<0.05) decreased PCV but not at 50 μg/kg level. GYP and GRE supplementation helped to overcome the negative effect of aflatoxin by increasing PCV compared to group C. There was no significant (p>0.05) effect on Hb, MCHC and glucose levels among various treatment groups. The weight of liver varied significantly (p<0.05) among the treatment groups but no change in heart, spleen and kidney weights were observed. The highest increase in the relative weight of liver was seen in the group fed aflatoxins at 2 mg/kg level. Supplementation GYP and GRE helped in reducing the liver enlargement effect of aflatoxins. In conclusion, GRE proved to be an effective alternative to GYP particularly at the rate of 2 mg/kg in providing protection against aflatoxin contaminated feed in broiler chicken.